A Cartographic Turnover: Geography in School and Visual Politics in the Epoch of Grand Utopias - Orlova, Galina (Voprosy obrazovaniya / Educational Studies Moscow, 2010)
In this article the reform of geography teaching in the mid-1930s is described in terms of geographic turnaround. Making the map a basis of school courses, converting geographic knowledge into a visual format, and concentrating attention on the cartographic skills of students is considered against the background of the principal symbolic events of the time. The transformation and transfiguration of Soviet reality takes places in the science of geography and involves nature, but it is due to the map that it gains visibility and credibility. This circumstance gives a more accurate description of the status of the new policy towards geography in school: it is a by-product of a (broadly understood) political use of geographic maps.